PEMBERIAN NAFKAH TERHADAP KELUARGA (Studi Kasus Aktifitas Khuruj Jama’ah Tabligh Di Kota Kendari) - Abdul Khawiyu (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
ABSTRACT This study is the Religious concept of the Jama'ah tabligh on the living during Khuruj fì sabilillah, the impact of the khaluj fi sabilillah on the living. The main source of data is the empirical data on the giving of the family to the family during the husband of Khuruj fì sabilillah in Kota Kendari, which is based on observations, interviews, and documentation. and society. Secondary sources are textbooks, internet or work by experts. To analyze the data using qualitative methods, where observation data, interviews and documentation are analyzed by qualitative method. Further on the unfolding of data analysis results communicated by theory then develops a comprehensive understanding of the concept of religion, the impact it creates Jama'ah Tabligh views the living as consisting of two bathiniyah which includes religious education for the family. While outward living is made up of material and biological. Material needs such as food and drink, household and household are the responsibility of a husband as the head of the family. Biological maintenance involves the relationship of husband and wife. Khuruj fìsabilllah has a positive and negative impact on children, wives and society. The existence of religious practices for wives, children and society has a positive impact. Having a displaced family has a negative impact. If a person follows the order of the people well, it will bring benefits and benefits for his or her people and the people. On the other hand, if a person prays to disobedience it will bring harm and slander to the individual and the people.